Quantifying Key Points of Hydraulic Vulnerability Curves From Drought-Rewatering Experiment Using Differential Method - Liu, Xiao; Wang, Ning; Cui, Rong; Song, Huijia; Wang, Feng; Sun, Xiaohan; Du, Ning; Wang, Hui; Wang, Renqing (Frontiers in Plant Science, 2021)
Precise and accurate estimation of key hydraulic points of plants is conducive to mastering the hydraulic status of plants under drought stress. This is crucial to grasping the hydraulic status before the dieback period to predict and prevent forest mortality. We tested three key points and compared the experimental results to the calculated results by applying two methods. Saplings (n = 180) of Robinia pseudoacacia L. were separated into nine treatments according to the duration of the drought and rewatering. We established the hydraulic vulnerability curve and measured the stem water potential and loss of conductivity to determine the key points. We then compared the differences between the calculated [differential method (DM) and traditional method (TM)] and experimental results to identify the validity of the calculation method. From the drought-rewatering experiment, the calculated results from the DM can be an accurate estimation of the experimental results, whereas the TM overestimated them. Our results defined the hydraulic status of each period of plants. By combining the experimental and calculated results, we divided the hydraulic vulnerability curve into four parts. This will generate more comprehensive and accurate methods for future research.